Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, dan Solvabilitas terhadap Opini Audit Going Concern - Handayani, Wuri Septi; Aulia, Syifa (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the effect of profitability, liquidity, company size, and solvability on going concern audit opinions Methodology: This research was conducted in the energy sector recorded on the Indonesia Stock Exchange for the 2018-2022 period. This study used the purposive sampling method, with samples obtained from as many as 55 companies. The analysis technique used in this study was logistic regression analysis with the analytical tool IBM SPSS ver. 22. Results: The results of this study show that profitability negatively affects going-concern audit opinion, and solvency has a positive effect on going-concern audit opinion. Meanwhile, liquidity variables and company size do not affect going-concern audit opinions. Limitations: The limitations of this study are that it only uses four variables: the object of research is limited to using energy sector companies, the period used is five years, and time, distance, and cost are limited. Contribution: This research is useful as information material and as a consideration for investors when making decisions to invest in a company. This study was conducted to examine variables that can influence going-concern audit opinions, thus assisting management in identifying risks and taking necessary actions to improve company operations.